Nanopores sensing and fundamental biological interactions - Iqbal, Samir M.; Bashir, Rashid; SpringerLink (Online service). (New York Springer Science, 2011)
Nanopores: Sensing and Fundamental Biological Interactions examines the emerging research directions surrounding nanopores such as genome sequencing and early disease detection using biomarker identification. Nanopores are nanometer scale holes formed naturally by proteins or cells, and can be used for a variety of applications, including sequencing DNA and detecting harmful chemicals such as anthrax. They can be integrated into artificially constructed encapsulated cells of silicon wafers while allowing small molecules like oxygen, glucose and insulin to pass. This book also: Discusses biological nanopores and solid-state nanopores Examines recent work on biological and synthetic nanopores Compares alternative approaches to nanopores including polymers, processes and protocols Covering the applications of nanopores in genetics, proteomics, drug discovery, early disease detection and detection of emerging environmental threats, Nanopores: Sensing and Fundamental Biological Interactions is a must-have book for biomedicalengineers and research scientists.
Bio-Nano Interactions -- Biological Nanopores -- Solid-state Nanopores -- Nanopore Fabrication Techniques -- Nanopores for DNA Sensing -- Nanopores for Protein Sensing -- Nanopores for Selective Detection -- Single Molecule Measurements -- Modeling of Nanopores -- Functional Membranes: Nanopore Arrays -- Alternate Approaches to Nanopores: Polymers, Processes and Protocols -- Biomimetic Functionality with Nanopores -- Outlook and Applications -- Conclusions.
Electronic reproduction.
Keywords: Nanotechnology; Nanoscience; Electronic books